2014
DOI: 10.1016/j.proeng.2014.10.131
|View full text |Cite
|
Sign up to set email alerts
|

Springback Analysis in Air Bending Process through Experiment based Artificial Neural Networks

Abstract: Sheet metal bending is one of the most frequently used sheet metal forming processes in manufacturing industry. This study investigates bending parameters and springback phenomenon of a stainless-steel sheet in air bending process. In most of the applications, springback is determined either by trial and error procedures or by using numerical methods. Artificial Neural Network (ANN) approach has proved to be a helpful tool for the engineers. ANN is used in this study to predict the springback amounts of stainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…It was observed that the BP neural network prediction model of the proposed PSO algorithm improved not only the accuracy of prediction, but also the learning speed of the network. Şenol et al [ 28 ] used ANN to predict the amounts of springback of stainless steel sheets through experiment-based networks. It was concluded that ANN can be effectively applied to determine springback in the air bending process.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the BP neural network prediction model of the proposed PSO algorithm improved not only the accuracy of prediction, but also the learning speed of the network. Şenol et al [ 28 ] used ANN to predict the amounts of springback of stainless steel sheets through experiment-based networks. It was concluded that ANN can be effectively applied to determine springback in the air bending process.…”
Section: Introductionmentioning
confidence: 99%
“…The results show ANN outperforming the regression models approach for the evaluated cases. The authors of [32] also investigated the effect of bending and springback angles in bending processes. In this case, experimental data obtained from FEA models was used to design and train the developed ANN models.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many studies have been aimed at understanding and reducing springback. Springback can occur in all bending methods: tube bending [5,6], L-bending [7][8][9], Ubending [10,11], press bending [12,13], V-bending [14,15], air bending [16,17].…”
Section: Introductionmentioning
confidence: 99%